Behavioral Economics and the Analysis of Consumption and Choice. (18th May 2015) - Hursh, Steven R.; Roma, Peter G.
Abstract : Behavioral economics (BE) in psychology focuses on the application of traditional microeconomics concepts to the study of behavior, particularly the cross‐species analysis of consumption broadly defined and choice. Here, we review key concepts such as demand, substitution, and complementarity within a behavioral psychology framework, novel behavioral economics analysis techniques for quantifying demand elasticity and patterns of choice behaviors, and broader implications for organizational decision‐making and empirical public policy. Copyright © 2015 John Wiley & Sons, Ltd.